Pier 21 : a history - Schwinghamer, Steven, 1976-; Raska, Jan (Mercury series., 2020)
"Between 1928 and 1971, nearly one million immigrants landed in Canada at Pier 21 in Halifax, Nova Scotia. During those years, it was one of the main ocean immigration facilities in Canada, including when it welcomed home nearly 400,000 Canadians after service overseas during the Second World War. In the immediate postwar period, Pier 21 became the busiest ocean port of entry in the country. Today, people across Canada still enjoy connections to Pier 21 through family history and stories of arrival at the site. Since 1998, researchers at the Pier 21 Interpretive Centre and now the Canadian Museum of Immigration have been conducting interviews, reviewing archival materials, gathering written stories, and acquiring photographs, documents, and other objects reflecting the history of Pier 21. This book builds upon the resulting collection. It presents a history of this important Canadian ocean immigration facility during its years of operation and later emergence as a site of public commemoration."--